PENDAMPINGAN DAN PENDAFTARAN BADAN HUKUM PERKUMPULAN RUMAH BELAJAR MIFASOL - Taupiqqurrahman; Muhammad Rifqi; Annisa Lisaana Sidqin Aliyya; Ryan Axel Pattiasina; Tatianna Daniella Usmany; Emir Febrian Marino; Faiz Aqiel Maulana Hidaya; Ferdinan Januari; Bayu Adi Rachmat; Yaumil Azza; Felicia Stefanie Setiawan (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2025)
The establishment of an association/community is part of the rights of every citizen. Regardless of where the youth live. One of the youth communities in Indonesia is a community in Depok City with the name of Rumah Mifasol Community. Rumah Mifasol focuses on the field of children's education. Rumah Mifasol is a form of answer to the many local children who have not received proper education. The birth of Rumah Mifasol became a change in the surrounding environment, especially for children who participated in learning activities to develop rapidly, such as children who are previously unable to read to be able to read. However, the community that has been established does not yet have a legal entity. The method used in this service is the Community Based Participatory Research or CBPR method, which is used by prioritizing the process of community participation in each activity. The results of the service of mentoring and registering the MiFasol Learning House Legal Entity have concrete steps and results. Where the association that was previously only an ordinary association, became an association that has a legal entity.